Gambaran Tingkat Pengetahuan Masyarakat tentang Penyakit Hipertensi di Desa Blu’uran Kabupaten Sampang - Mery Eka Yaya Fujianti; Desi Holifatus Su’aida (Institut Nalanda, 2026)
Hypertension is a non-communicable disease that has become a major public health problem because it can cause serious complications if not properly managed. This study aimed to describe the level of community knowledge about hypertension in Blu’uran Village, Sampang Regency. This study used a quantitative method with a descriptive cross-sectional design involving 32 respondents selected using a simple random sampling technique, and the data were analyzed univariately using IBM SPSS Statistics. The results showed that most respondents were female, totaling 18 respondents (56.25%), and the highest level of education was junior high school with 14 respondents (43.75%). The level of community knowledge about hypertension was categorized as sufficient in 13 respondents (40.625%), good in 9 respondents (28.125%), and poor in 10 respondents (31.25%). These results indicate that there are still people with low levels of knowledge regarding hypertension. The level of community knowledge is influenced by several factors such as education, access to information, and individual experiences related to health problems. Good knowledge about hypertension can increase public awareness in implementing healthy lifestyles and carrying out early prevention of hypertension. The level of community knowledge about hypertension in Blu’uran Village, Sampang Regency was mostly in the sufficient category, therefore education and health promotion efforts are needed to increase public awareness in preventing hypertension and its complications.